Transversal literacy for higher education curriculums: Academic Literacy through the Production of Academic and Professional Discursive Genres - Burbano Pedraza, María del Cielo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This lecture offers the elements to mainstream literacy in different higher education curricula. It starts from the premise that all professions are fields of power, and that access to them lies especially in the domain of their discursive genres. This article presents the methodology of the strategy from the experience of its application in an academic program of Public Accounting. It graphically condenses and presents seven superstructures provided to students, including a professional discursive genre. The results are offered through a qualitative assessment of the strategy based on focus groups and brief interviews with students, teachers and managers. Fundamental recommendations are added for the continuous improvement of the process.